(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article is intended to discuss the causes of heart and vascular diseases, clinical treatment, application of modern treatment methods in this disease, and the use of modern techniques.